By the Sea, much more than a sculpture: Dominga! - Nunes , Fabíola Fraga; Campagnaro, Rodrigo Vianna (Farol, 2025)
This article aims to address the sociocultural and historical aspects of public monuments in the city of Vitória. To this end, it will investigate the sculpture of Dona Dominga, a figure known to her contemporaries, yet practically invisible over time, as it "lies" on the steps of the Espírito Santo State Government Palace, with a landscape of a city that flows anonymously with no time for contemplation and Vitória Bay, the monument’s main view. To this end, a "dialogue" with the work’s author, the Italian Carlo Crepaz, will be essential, albeit through the details of its creation, since he is now deceased. From this perspective, we intend to lay bare the citizen Domingas, the worker, the woman, and finally bring to light a character reflected in so many others in our daily lives, with equal or greater erasure, forgotten by the seaside... Drawing on available public information, as well as official documents, this work will have as its central objective to transform a motionless and inanimate object into a living expression of Brazilian, Espírito Santo, and peripheral resistance, truly present today, a fundamental component of the urban mosaic of downtown Vitória.